BUILDING A MARKETING STRATEGY IN ENHANCING SALES, PROFITABILITY AND FINANCIAL FEASIBILITY OF A NEW BUSINESS A CASE STUDY ON SALTED EGG SAUCE NEW BUSINESS: "DOUBLE WUENAK" (DW) - Petrus Pius Salamin; Dewi Ayu (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2018)
Tujuan penelitian – This analysis aims to know the market opportunity, and what marketing strategy to be applied which has impact on enhancing sales, profitability and financial feasibility of this new business.Metode Penelitian - The data used in this analysis is the projection data which is based on market prices this moment, and the price projected for the next five (5) years. Method used in determining market opportunity, and sales projection is opinion method both from the owners it self and the marketer, and methods of experiment and market survey. Methods used in determining the financial feasibility are Prsent Value (NPV), Profitability Index (PI), Payback Period, and Average Rate of Return (ARR). In enhancing sales, profitability and financial feasibility of this new business it must be supported by an oppropriate marketing strategy (Prduct, Price, Distribution and Promotion strategies).Temuan - The result of market opportunity analysis supported by an appropriate marketing strategy shows that this busniness is feasible. Potensial market/consummers at the first year (2018) is  4.800, and it will increase to 11.520 in 2022, with an average growth of 25% per year. In according to the potential market above, the revenue form sales in 2018 is projected Rp 312.000.000, and it will increase to Rp 864.000.000 in 2022, with an average growth of 29% per year. In line with the above sales, as shown in Pro Forma  Income Statement, this business is gaining net profit Rp 48.450.680 in 2018, and it will increase to Rp 451.266.023 in 2022, with an average growth of 76.6% per year. Using the investment criterions such as Net Present Value, Paybak Period,  Profitability Index, and Average Rate of Return to measure its financial feasibility, this business is feasible. The NPV is positive, and PI  > 1,  ARR is 391.1% (3.91), while the Payaback Period is only  1 year and 0. 2 month.Keterbatasan penelitian - The limitation of this analysis is that it focus on a case, and future projection may be affected by future changes in external factors.Kata Kunci: Market Opportunities, marketing strategy and Financial Feasibility (NPV, PI, Payback Period, and ARR)